2013
DOI: 10.1089/cap.2012.0121
|View full text |Cite
|
Sign up to set email alerts
|

Skin Rash Occurring with Olanzapine Pamoate, but not with Oral Olanzapine, in a Male with Juvenile Idiopathic Arthritis

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Other studies of patients with anxiety disorders have found evidence of this altered amygdala connectivity, specifically in youth (Hamm et al, 2014; Swartz, Phan, Angstadt, Fitzgerald, & Monk, 2014). Schizophrenia patients also show altered amygdala activity during social tasks and facial recognition studies, with a higher activation to neutral faces and lower activation to fearful ones as compared to controls (Mier et al, 2014; Morris et al, 1996; Mukherjee et al, 2013; Solfanelli et al, 2013). This has led to the hypothesis that dysfunction of the amygdala is closely related to the social impairments seen in schizophrenia patients due to inappropriate activation to normally non-fearful social stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of patients with anxiety disorders have found evidence of this altered amygdala connectivity, specifically in youth (Hamm et al, 2014; Swartz, Phan, Angstadt, Fitzgerald, & Monk, 2014). Schizophrenia patients also show altered amygdala activity during social tasks and facial recognition studies, with a higher activation to neutral faces and lower activation to fearful ones as compared to controls (Mier et al, 2014; Morris et al, 1996; Mukherjee et al, 2013; Solfanelli et al, 2013). This has led to the hypothesis that dysfunction of the amygdala is closely related to the social impairments seen in schizophrenia patients due to inappropriate activation to normally non-fearful social stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the single case reports, two of them were based on the description of side effects [ 44 , 45 ]. Mirza et al [ 45 ] described a male adolescent inpatient with schizophrenia who developed a severe acute-onset delirium after the second dose of LAI paliperidone (first dose: 150 mg and second: 100 mg).…”
Section: Resultsmentioning
confidence: 99%
“…None of the previous reports had described the postpartum onset of acneiform dermatoses on exposure to olanzapine. Skin rash, [7] pustular eruptions, [8] hypersensitivity syndrome, [9] acneform eruptions, [7] and pellagroid skin eruptions have been reported with oral olanzapine preparation [10] in non-postpartum cases. Pathological findings have confirmed the nature of the skin eruption after olanzapine exposure [11] in non-postpartum cases.There is no previous case report describing postpartum acneiform dermatosis with olanzapine exposure in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%